Pemberian Motivasi Terkait Ekonomi Kreatif Kepada Masyarakat Desa Muara Botung - Ahmad Sayuti Pulungan; Makhrani Makhrani; Nursalamah Nursalamah; Lailan Syafrina Hasibuan (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The abstract contains a brief description of the problem and research objectives, the method used. This community service activity (PkM) was carried out in Kotanopan District, Mandailing Natal Regency. The aim of this PkM is to build community motivation in developing the creative economy in the area where they live. The implementation of this activity was carried out using the lecture and question and answer method. The purpose of the lecture method is to provide understanding and explain why a creative economy is needed. Furthermore, in this dedication, it is explained about other methods by observing, imitating and modifying. Furthermore, it is also explained in this service in the form of examples of villages that have developed a creative economy based on their potential.